2023
DOI: 10.1164/rccm.202208-1543oc
|View full text |Cite
|
Sign up to set email alerts
|

The Long-Term Impact of Early-Life Tuberculosis Disease on Child Health: A Prospective Birth Cohort Study

Abstract: Rationale There is growing concern that post–tuberculosis disease (TB) sequelae and morbidity are substantial, but no studies have controlled for preexisting factors before disease. Whether children have post-TB morbidity is not well characterized. Objectives To assess the effect of a TB diagnosis on wheezing episodes, lung function, and anthropometric measurements among children enrolled in a prospective birth cohort study in South Africa. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 38 publications
1
30
0
Order By: Relevance
“…Only one included study performed non-spirometry PFTs, they instead reported association coefficients between childhood PTB occurring between one to four years of age with measurements taken at the age of five, as presented in appendix VI. 25…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Only one included study performed non-spirometry PFTs, they instead reported association coefficients between childhood PTB occurring between one to four years of age with measurements taken at the age of five, as presented in appendix VI. 25…”
Section: Resultsmentioning
confidence: 99%
“…22 A total of 567 children with history of PTB were included; median number of children in studies was 68 (range: 42-305). [21][22][23][24][25] Key characteristics were reported in Table 1, and details of quality scores shown in appendix IV. One study performed non-spirometry PFTs after early-life TB, 25 thus excluded from meta-analyses.…”
Section: Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this issue of the Journal , Martinez and colleagues (pp. 1080–1088 ) offer a breath of fresh air as they begin to fill the unacceptable pediatric PTLD evidence gap ( 14 ). This unique analysis leverages data provided by the Drakenstein birth cohort study in South Africa that is composed of 1,068 mother-infant pairs living in a high TB and HIV–burden, economically disadvantaged community.…”
mentioning
confidence: 99%